Growth measurements from corals in an ocean-based nursery experiment near Sambangan Island, Indonesia, 2003-2004 - Sebastian C A Ferse (PANGAEA, 2019)
This dataset contains growth measurements of corals in ocean-based nurseries. The data derives from coral growth experiments based near Sambangan Island, Indonesia, conducted from October 2003 to March 2004. In this study, the use of cages built from locally available materials in the ocean-based culture of fragments of the coral species Acropora gomezi and Pavona cactus was examined. In a first experiment, fragments were cultured without cages, within concrete frames with bamboo covers of two different mesh sizes, and within control cages at two different depths. In a second experiment, fragments were reared inside concrete frames covered with fishing net, half of which were additionally shaded with bamboo covers. Growth rates were measured every three weeks as linear increases and at the end of the experiments as increases in weight and volume. For size measurements a steel caliper (accuracy 0.1 mm) was used, the weight was measured with an electronic solar letter scale with an accuracy of 0.5 g (MAULtronic S). Volume was measured by suspending the fragments up to the base into a plastic cylinder with a ml scale (Ø 27 mm) which was filled to the rim with sea water or by measuring the water displacement in a larger beaker.